IDENTIFIKASI FOKUS MIKROSKOP DIGITAL MENGGUNAKAN METODE OTSU - Putranto, Ari Bawono; Adi, Kusworo; Gernowo, Rahmat (BERKALA FISIKA, 2014)
A study to identify focus on a digital microscope has been done using a threshold value of the object microscope image obtained by Otsu method. Microscope image of the object captured by the change from a maximum to a minimum distance between the object and the microscope objective lens to record the amount of movement of a motor stepper and calculates the Otsu threshold value on each image. Based on data from a Otsu threshold value of each microscope image of the object to the changes within the object can be inferred the existence of a relationship between the position of an object to focus the microscope with the image of the threshold value that is increasingly the focus of an image , the image of the Otsu threshold values ​​obtained are also getting smaller. In this study done by testing two samples as objects of microscope that single hair samples and samples collection of several hairs were each placed on a microscope glass slide. Data collection and observation results show that for a single hair samples obtained object focus Otsu threshold value T = 97 and sample an object consisting of a collection of some of the hair is obtained Otsu threshold value T = 127. But the testing of two samples showed differences influenced by the ratio between the number of pixels on the image and the background image of an object caused by the influence of the intensity of the light source of the microscope. Keywords: Focus Identification, Digital Microscope, Otsu Threshold